2017
DOI: 10.1097/qai.0000000000001526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SMS/GPRS Printers in Reducing Time to Early Infant Diagnosis Compared With Routine Result Reporting: A Systematic Review and Meta-Analysis

Abstract: Background:Despite significant gains made toward improving access, early infant diagnosis (EID) testing programs suffer from long test turnaround times that result in substantial loss to follow-up and mortality associated with delays in antiretroviral therapy initiation. These delays in treatment initiation are particularly impactful because of significant HIV-related infant mortality observed by 2–3 months of age. Short message service (SMS) and general packet radio service (GPRS) printers allow test results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…28 In a 2016 systematic review, 29 the effect of mHealth interventions on improving PMTCT and early infant diagnosis was summarised from five studies, with a significant increase reported in early infant diagnosis uptake at 6 weeks post partum (pooled relative risk 1·2, 95% CI 1·1–1·3). Findings of a 2017 systematic review 30 ascertained that SMS and general packet radio service (GPRS) printers reduced turnaround time for infant PCR test results by 25% compared with a paper-based courier (51·1 days vs 68·0 days). Our trial provides the most comprehensive evidence to date of the success of an mHealth intervention to improve quality and efficiency across the complete early infant diagnosis cascade of care.…”
Section: Discussionmentioning
confidence: 99%
“…28 In a 2016 systematic review, 29 the effect of mHealth interventions on improving PMTCT and early infant diagnosis was summarised from five studies, with a significant increase reported in early infant diagnosis uptake at 6 weeks post partum (pooled relative risk 1·2, 95% CI 1·1–1·3). Findings of a 2017 systematic review 30 ascertained that SMS and general packet radio service (GPRS) printers reduced turnaround time for infant PCR test results by 25% compared with a paper-based courier (51·1 days vs 68·0 days). Our trial provides the most comprehensive evidence to date of the success of an mHealth intervention to improve quality and efficiency across the complete early infant diagnosis cascade of care.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should be conducted on ways to strengthen sputum collection transportation and testing the NTP would need to know why delivery of results back to requesting facilities was such a challenge so as to put in appropriate measures in ensuring adherence to national guidelines on sputum collection, transportation and delivery of results. The NTP would need to explore if modern technologies such as a short message services (SMSs) which has improved result turn-around times in early infant diagnosis as compared to courier-based reporting would improve the challenges in the programme [ 10 ]. This may ultimately improve treatment outcomes as patients receive results on time.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are also offered provider-initiated HIV testing services in the MDR-TB pre-treatment phase and those found to be HIV positive are assessed for initiation on antiretroviral therapy (ART) and cotrimoxazole preventive therapy (CPT). As per the national guidelines in use during the study period, they were initiated on a fixed-dose combination once-daily pill of Tenofovir v+ Lamuvidine (or Emtricitabine) + Efavirenz (TDF+3TC) or (FTC)+EFV) as the preferred first-line ART regimen among adult PLHIV and abacavir+ lamuvidine + efavirenz or (Lopinavir/r) (ABC + 3TC + EFV (or Lop/r)) as the preferred first-line ART regimen in children living with HIV [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Post-NTBRL leakages in SL-DST results may be reduced if the NTP introduces electronic reporting to increase both speed and access to SL-DST results by health facilities. Short message services (SMSs) have improved result turn-around times in early infant diagnosis as compared to courier-based reporting (Vojnov et al, 2017). The NTP may also consider investing in point-of-care diagnostics that offer sensitivity patterns to FQ and SLIs even in peripheral areas to ensure equity of access to SL-DSTs (Xie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%